Regulation of Human Natural Killer Cell IFN-γ Production by MicroRNA-146a via Targeting the NF-κB Signaling Pathway - Wang, Hongwei; Zhang, Yibo; Wu, Xiaojin; Wang, Yufeng; Cui, Hanwei; Li, Xinxin; Zhang, Jianying; Tun, Norman; Peng, Yong; Yu, Jianhua (Frontiers in Immunology, 2018)
Natural killer (NK) cells are one group of innate lymphocytes that are important for host defense against malignancy and viruses. MicroRNAs (miRNAs) play a critical role in regulating responses of immune cells including NK cells. Accumulating evidence suggests that miR-146a is involved in the regulation of immune responses. However, the mechanism by which miR-146a regulates NK cell function is largely unknown. In the current study, we found that miR-146a intrinsically regulated NK cell function. Forced overexpression of miR-146a decreased IFN-γ production, whereas downregulation of miR-146a by anti-miR-146a significantly enhanced IFN-γ production in the human NK-92 cell line and primary human NK cells upon stimulation with IL-12 or co-stimulation with IL-12 and IL-18. Mechanistically, miR-146a regulated IFN-γ production via NF-κB, as evidenced in NK-92 cells, by downregulation of NF-κB p65 phosphorylation when miR-146a was overexpressed but upregulation of NF-κB p65 phosphorylation when anti-miR-146a was overexpressed. miR-146a directly targeted IRAK1 and TRAF6, the upstream signaling components of the NF-κB signaling pathway. This direct targeting mechanism confirmed the above gain- and loss-of-function approaches. However, the potent IFN-γ-producing subset, CD56bright NK cells, expressed higher levels of miR-146a than the lesser IFN-γ-producing subset, CD56dim NK cells. We also observed that co-stimulation of IL-12 and IL-18 significantly increased miR-146a expression in bulk NK cells and in the CD56bright subset in a time-dependent manner, correlating with augmented IFN-γ production. These data suggest that miR-146a plays a negative role in IFN-γ production by human NK cells and this miRNA may be critical in preventing NK cells from being super activated and overproducing IFN-γ.